2022
DOI: 10.3390/ijerph192316320
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome and COVID-19 Lockdown: Research on Residential Care Workers Who Assume Parental Roles with Youths

Abstract: Healthcare professionals are at higher risk of developing and experiencing burnout. Parents may also suffer from prolonged stressful conditions that lead to physical and emotional exhaustion. Residential youth care workers assume a caregiving role that can lead to persistent stressful conditions that affect their relationship with the youth. In addition, the COVID-19 lockdown has had a negative impact on both the organization and the work, as well as on the lifestyle of workers and minors. In fact, during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 47 publications
4
11
1
1
Order By: Relevance
“…This finding is consistent with earlier research conducted by García [ 30 ], which highlights health-care personnel as a vulnerable group in the pandemic response, with 20% of COVID-19 cases attributed to frontline health-care workers. Our study also aligns with the literature, such as Sheehan et al [ 31 ], Ferro et al [ 32 ], and Caillet et al [ 33 ], who reported a higher prevalence of characteristics related to burnout symptoms among female undergraduate interns. Variations in specific staffing characteristics were noted, such as those based on residential care workers, emergency department staff, or intensive care unit staff.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with earlier research conducted by García [ 30 ], which highlights health-care personnel as a vulnerable group in the pandemic response, with 20% of COVID-19 cases attributed to frontline health-care workers. Our study also aligns with the literature, such as Sheehan et al [ 31 ], Ferro et al [ 32 ], and Caillet et al [ 33 ], who reported a higher prevalence of characteristics related to burnout symptoms among female undergraduate interns. Variations in specific staffing characteristics were noted, such as those based on residential care workers, emergency department staff, or intensive care unit staff.…”
Section: Discussionsupporting
confidence: 92%
“…For stressful situations to be managed in relation to the minor and the complex care organization in which he/she is incorporated, this could concern the ability to respond adaptively to events and apply useful and effective coping strategies, such as asking for support when necessary, having a positive attitude or planning properly for the implementation of targeted and effective interventions. Our earlier study showed that the use of avoidance strategies appears to be increasing among social and health care workers in the face of greater emotional intolerance [14].…”
Section: Instrumentsmentioning
confidence: 89%
“…In addition, burnout conditions can cause frequent turnover, which negatively impacts children who have already experienced relationship breakdowns and losses [15]. In addition, it appears that under these conditions, there is a tendency to become emotionally detached, to use avoidance strategies and to reduce the ability to regulate emotions [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations